A very rare case report of glycogen storage disease type IXc with novel PHKG2 variants - Yongxian Shao; Taolin Li; Minyan Jiang; Jianan Xu; Yonglan Huang; Xiuzhen Li; Ruidan Zheng; Li Liu (BMC, 2022)
Abstract Background Pathogenic mutations in the PHKG2 are associated with a very rare disease-glycogen storage disease IXc (GSD-IXc)-and are characterized by severe liver disease. Case presentation Here, we report a patient with jaundice, hypoglycaemia, growth retardation, progressive increase in liver transaminase and prominent hepatomegaly from the neonatal period. Genetic testing revealed two novel, previously unreported PHKG2 mutations (F233S and R320DfsX5). Functional experiments indicated that both F223S and R320DfsX5 lead to a decrease in key phosphorylase b kinase enzyme activity. With raw cornstarch therapy, hypoglycaemia and lactic acidosis were ameliorated and serum aminotransferases decreased. Conclusion These findings expand the gene spectrum and contribute to the interpretation of clinical presentations of these two novel PHKG2 mutations.